Implementación de indicadores e índices de gestión en una camaronera de 50has de producción en la provincia de El Oro. - Ortega Pesantes, Gina Karina (My University, 2019)
Shrimp activity in the province of El Oro and at the national level generates high levels of economic income, the shrimp is one of the main products of the non-oil trade balance, and that is why the government offers incentives for participation in this activity. This research was carried out with the objective of implementing indicators for management evaluation in GINAMAR; Through a descriptive methodology, the study was carried out in three stages that were supported by the documentary analysis of articles in scientific journals to carry out the theoretical foundation and the application of an interview for the initial exploration of the problem, and after the analysis of the Data were identified which indicators and indices of management for shrimp farms exist, then they were determined which were to be evaluated, and in the end the evaluation model of Content Validity Reason was identified that will allow quantifying and describing the quality of management. Through the results it was shown that the management in the company has a medium level of effectiveness, needs to improve in twelve items and especially focus on improving the updating of technical knowledge and the preparation of staff. A flexible methodology for the evaluation of management indicators has been implemented that analyzes thirty items corresponding to fifteen indicators contained in eight perspectives, allowing to conclude that this system is feasible to apply for the improvement of management.
La actividad camaronera en la provincia de El Oro y a nivel nacional genera altos niveles de ingresos económicos, el camarón es uno de los principales productos de la balanza comercial no petrolera, y es por ello que el gobierno ofrece incentivos para la participación en esta actividad. Esta investigación se realizó con el objetivo de implementar indicadores para la evaluación de la gestión en GINAMAR; a través de una metodología descriptiva, el estudio se ejecutó en tres etapas que se apoyaron del análisis documental de artículos de revistas científicas para realizar la fundamentación teórica y la aplicación de una entrevista para la exploración inicial de la problemática, y posterior al análisis de los datos se identificaron qué indicadores e índices de gestión para camaroneras existen, luego se determinaron cuáles se iban a evaluar, y al final se identificó el modelo de evaluación Razón de Validez de Contenido que permitirá cuantificar y describir la calidad de la gestión. A través de los resultados se evidenció que la gestión en la empresa tiene un nivel de efectividad mediano, necesita mejorar en doce ítems y sobre todo enfocarse en la mejora de la actualización de conocimientos técnicos y la preparación del personal. Se ha implementado una metodología flexible para la evaluación de indicadores de gestión que analiza treinta ítems correspondientes a quince indicadores contenidos en ocho perspectivas, permitiendo concluir que este sistema es factible de aplicar para el mejoramiento de la gestión.
Keywords: ACTIVIDAD CAMARONERA; EVALUACIÓN DE LA GESTIÓN; RAZÓN DE VALIDEZ DE CONTENIDO